2002
DOI: 10.1046/j.1365-2273.2002.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of endonasal KTP laser dacryocystorhinostomy versus external dacryocystorhinostomy

Abstract: We retrospectively reviewed all primary external dacryocystorhinostomies (DCRs) and endonasal KTP laser DCRs performed for epiphora as a result of nasolacrimal duct obstruction in our unit between 1993 and 2000. Forty-nine patients underwent an external approach and 76 endonasal laser procedures were performed. The success rate of the external group was 94% with a mean follow-up of 9 months. In contrast, the endonasal group's success rate was 64% with a mean follow-up of 12 months. This difference reached stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 16 publications
4
47
0
1
Order By: Relevance
“…The success rate in case of Group II was 76% (19 cases) and 6 cases (24%) were failure. 4 Ibrahim et al 12 and Mirza et al 13 However, when compared to Cokkesser et al, 11 Dolman P. J 10 and Tsirbas et al, 5 our Endoscopic DCR group has a lower success rate.…”
Section: Success Ratementioning
confidence: 76%
“…The success rate in case of Group II was 76% (19 cases) and 6 cases (24%) were failure. 4 Ibrahim et al 12 and Mirza et al 13 However, when compared to Cokkesser et al, 11 Dolman P. J 10 and Tsirbas et al, 5 our Endoscopic DCR group has a lower success rate.…”
Section: Success Ratementioning
confidence: 76%
“…Similarly, Watts et al (2001) reported a success rate of 94.7% in 19 patients at 12 months and Mirza et al (2002) reported a success rate of 94% in 49 patients after a mean follow-up of 9 months. All the surgeons in the above studies were highly experienced, with at least 10 years of experience in ophthalmology (Watts et al, 2001;Mirza et al, 2002;Besharati et al, 2005;Karim et al, 2011). In a study similar to ours, Besharati et al (2005) reported success rates of 88% in 149 patients in a teaching hospital in Iran, with a follow-up range of 3 months to 2 years.…”
Section: Discussionmentioning
confidence: 89%
“…Mirza et al (2002) found an improved outcome in the last 38 cases of endonasal DCR out of a total of 76 cases but did not explicitly mention data documenting the learning curve. Surprisingly, no study till date has evaluated the learning curve in detail (Mirza et al, 2002;Pandya et al, 2010;Malhotra, 2015;Kashkouli et al, 2003). Ours was a unique study in which we compared the results of external DCR surgery by a trainee ophthalmologist over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Basically, it is a bypass surgery in which obliterated nasolacrimal duct is bypassed and lacrimal sac is opened directly into the nasal cav- ity. Traditionally this operation is done via an external approach with high success rates (82-99%) [4][5][6][7][8][9][10][11]. In spite of such good results, the procedure has various disadvantages like eksternal skin incision and scar, excessive intra-operative bleeding, disruption of the medial canthus anatomy, long surgical time and high morbidity [12].…”
Section: Resultsmentioning
confidence: 99%